The developmental and genetic trajectory of coloration in the guppy (Poecilia reticulata). Issue 6 (6th September 2018) - Dick, Cynthia; Arendt, Jeff; Reznick, David N.; Hayashi, Cheryl Y.
Abstract : Examining the association between trait variation and development is crucial for understanding the evolution of phenotypic differences. Male guppy ornamental caudal fin coloration is one trait that shows a striking degree of variation within and between guppy populations. Males initially have no caudal fin coloration, then gradually develop it as they reach sexual maturity. For males, there is a trade‐off between female preference for caudal fin coloration and increased visibility to predators. This trade‐off may reach unique endpoints in males from different predation regimes. Caudal fin coloration includes black melanin, orange/yellow pteridines or carotenoids, and shimmering iridescence. This study examined the phenotypic trajectory and genetics associated with color development. We found that black coloration always developed first, followed by orange/yellow, then iridescence. The ordering and timing of color appearance was the same regardless of predation regime. The increased expression of melanin synthesis genes correlated well with the visual appearance of black coloration, but there was no correlation between carotenoids or pteridine synthesis gene expression and the appearance of orange/yellow. The lack of orange/yellow coloration in earlier male caudal fin developmental stages may be due to reduced expression of genes underlying the development of orange/yellow xanthophores.